PARADOKSALITAS PEMOSISIAN PEREMPUAN NOVEL COLOMBA KARYA PROSPER MERIMEE - Udasmoro, Wening (Sekolah Pascasarjana UGM, 2015)
Women have been narrated by men authors since classical literature; this has continued into contemporaryliterature. In the 19th century, many authors were interested in narrating and positioning women intheir novels. This period can be considered one of transition, in which traditionality and modernity werecontested because of influences from the industrial revolution and many other social movements inEurope. This period was also one of challenge, with the appearance of Gustave Flaubertâs novel MadameBovary, which was questioned because of moralistic issues. If in the early 19th century traditionalitywas represented by EugÃ©nie Grandet and Balzacâs figures of woman, but in the middle of the centuryFlaubert dealt with freedom of sexuality, what discourses were presented in between these two differentperiods? This article aims at explaining the bridging of the gap between the symbols of traditionalityand modernity, especially through the representation of women. MÃ©rimÃ©eâs novel, Colomba, depicts theagency of a woman named Colomba. In this novel, MÃ©rimÃ©e not only showed the position of women visÃ vis men in parental or conjugal relation, like in the novels EugÃ©nie Grandet or Madame Bovary. Rather,the author attempted to look at the relationship between masculinities and femininities in a Corsicancontext, in which the intersection of gender and social class (as well as traditions) was different than inthe Parisian context. The relation between the novel and the social structure in the 19th century Europeplays an important part in the discussion and explanation of the relationship between the literature andsocial narration of that period